On the Effect of State fragility on Corruption - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2014)
The Kodila-Tedika & Bolito-Losembe (2014, ADR) finding on no evidence of causality flowing from State fragility to classical corruption or extreme corruption could have an important influence on academic and policy debates. Using updated data (1996-2010) from 53 African countries, we provide evidence of a positive (negative) nexus between political stability/no violence and corruption-control (corruption). As a policy implication, the finding of the underlying paper maybe more expositional than factual and should be treated with caution.
Keywords: F52; K42; O17; O55; P16; 330; Fragility; Corruption; Conflicts; Africa